The significance of CD16+ monocytes in the occurrence and development of chronic thromboembolic pulmonary hypertension: insights from single-cell RNA sequencing - Chen, Maohe; Wu, Qiuxia; Shao, Nan; Lai, Xingyue; Lin, Huo; Chen, Min; Wu, Yijing; Chen, Jiafan; Lin, Qinghuang; Huang, Jiahui; Chen, Xiaoyun; Yan, Wei; et al. (Frontiers in Immunology, 2024)
Chronic thromboembolic pulmonary hypertension (CTEPH) is a complex condition with unclear pathogenesis. We used single-cell RNA sequencing to characterize monocytes in CTEPH patients. We found a significant increase in the CD16+ monocyte subset, which had unique transcriptomic features related to cell adhesion, T cell activation, coagulation, and platelet activation. These features suggest a pivotal role in pulmonary artery thrombus formation and remodeling. We also observed pro-inflammatory macrophage subsets in the tissues from CTEPH patients after pulmonary endarterectomy (PEA). These macrophages showed lipid metabolism reprogramming, which may contribute to thrombus persistence and pulmonary artery intimal remodeling. Notably, we identified a subpopulation of macrophages that differentiated from CD16+ monocytes and highly expressed IL‐1β. This subpopulation was associated with disease progression. Our study reveals the involvement of CD16+ monocytes in CTEPH and presents potential therapeutic targets for intervention.